EVALUATION OF TWO ENZYMATIC FIBROLYTIC COMMERCIAL COMPLEXES ON DIGESTIBILITY AND DIGESTION KINETICS OF SUGARCANE BUD (Saccharum officinarum) - Delgado S., José (2014)
The effect of two commercial enzymes (Allzyme Vegpro® and RovabioTM Excel) onthe in situ digestibility and kinetics of the dry matter of sugarcane bud (Saccharumofficinarum) was evaluated. The substrate was dried, grounded, passed through a 3 mmsieve, and incubated with the enzymes for 30 minutes. The concentration of the enzymeswas 1% of the substrate. In addition, a substrate without treatment was considered ascontrol treatment. A randomized experimental design, with four periods, three treatmentsand two replicates per period was used. The samples (1.8 g) in dracon bags were placedin the first stomach compartment of one fistulated alpaca and six digestion times (6, 12,24, 48, 72 and 96 h) were applied. The parameters evaluated in digestion kinetics wereinitial digestibility, degradable fraction, degradation rate, potential digestion and averagetime. The dry matter (ISDMD) in situ digestibility did not improve; however statisticaldifferences (p<0.05) were found at 6, 12 and 48 hours but without biological significance.There were no differences among treatments for the studied variables. It is concludedthat the dose used of fibrolytic enzymes does not increase digestibility or kinetics ofdigestion of sugarcane bud.